Simulating the performance of green walls on temperature changes in urban open spaces: a case study of a traditional green wall on Shahid Mousavi street in Tehran - Maryam Azmoodeh (مهندسی و مدیریت ساخت, 2022)
Today's cities are narrowing the field for the presence of citizens in the city due to the many problems they impose on their citizens. In order to provide a suitable environment for the presence of residents in the streets and urban spaces, the urban space must provide minimum conditions of comfort for people. A space where the temperature is comfortable and annoying factors such as air pollution and noise pollution are small. One of the solutions that can play an effective role in this field is the return of nature to the urban space and reestablishing a balanced cycle of climatic parameters. The use of vegetated green surfaces can be considered an important solution in reducing the temperature in hot seasons through shading and the cooling effect of plants. In addition to the mentioned issues, the aesthetic aspect of these walls can also improve people's psychological comfort and help the presence of people in the urban space. The current research has been conducted with the aim of investigating the effect of green surfaces on temperature changes in urban open spaces, and through simulation with Envi-met program, this issue has been investigated more deeply. The results of these studies showed that in hot seasons, the air temperature around the green walls decreases significantly, and in cold seasons, the temperature is slightly higher than the points with a distance from the wall.